Size and Composition Dependence of Oxygen Reduction Reaction Catalytic Activities of Mo-Doped PtNi/C Octahedral Nanocrystals - Polani, Shlomi; MacArthur, Katherine E.; Klingenhof, Malte; Wang, Xingli; Paciok, Paul; Pan, Lujin; Feng, Quanchen; Kormányos, Attila; Cherevko, Serhiy; Heggen, Marc; Strasser, Peter (ACS Catalysis, 2021)
A variety of synthesis protocols for octahedral PtNi nanocatalysts have led to remarkable improvements in platinum mass and specific activities for the oxygen reduction reaction. Nevertheless, the values achieved are still only one tenth of the activity measured from Pt3Ni single-crystal (111) surfaces. These particles lose activity during potential cycling, primarily because of Ni leaching and subsequent loss of shape. Here, we present the syntheses and high catalytic oxygen reduction reaction activities of molybdenum-doped PtNi octahedral catalysts with different sizes (6-14 nm) and compositions. We show that the Mo-doped, Ni-rich, PtNi octahedral catalysts exhibit enhanced stability over their undoped counterpart. Scanning transmission electron microscopy with energy-dispersive X-ray analysis reveals the particular elemental distribution for the size and composition of the different catalysts. By combining high-resolution compositional analysis with electrochemical measurements and online inductively coupled plasma mass spectrometry, it was possible to correlate the size, morphology, and composition with the oxygen reduction reaction activities before and after accelerated stress tests. The octahedral catalysts show high electrochemical surface areas and increasing specific activity with increasing surface area of the (111) facets and Ni content, leading to high mass activities. These results demonstrate the advantages of increasing the (111) surface area and Ni content of PtNi nano-octahedral catalysts to improve the performance and stability for the oxygen reduction reaction.
CRIS-Team Scopus Importer:2024-12-16
Keywords: metal dissolution; oxygen reduction; PtNiMo octahedra; stability; synthesis